2015
DOI: 10.1080/17430437.2015.1067781
|View full text |Cite
|
Sign up to set email alerts
|

Men in a ‘women only’ sport? Contesting gender relations and sex integration in roller derby

Abstract: Roller derby is a growing, popular sport, where teams compete on roller skates, and where rules allow "blocking" and full body contact. Roller derby is primarily played by women, with men restricted to support roles during its revival stage in the early 2000s. However, men and gender diverse skaters are increasingly playing the sport, in mixed / co-ed leagues and Men's teams. This has created deep divisions within the derby community regarding the role of men in a women's space and the playing of a full contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Research participants’ theatrical backgrounds in dance studies allowed them to be welcomed and prevented them from being scrutinized by female members of the studio. Contrary to women participating in female-centered activities, research has shown that women expressing strong passion for their involvement expands to exclusiveness, which ultimately renders the feeling that men are invading a female terrain (Pavlidis and Connor, 2016). In this study, it was not mentioned why studio owners restricted access for certain men to join classes.…”
Section: Discussionmentioning
confidence: 99%
“…Research participants’ theatrical backgrounds in dance studies allowed them to be welcomed and prevented them from being scrutinized by female members of the studio. Contrary to women participating in female-centered activities, research has shown that women expressing strong passion for their involvement expands to exclusiveness, which ultimately renders the feeling that men are invading a female terrain (Pavlidis and Connor, 2016). In this study, it was not mentioned why studio owners restricted access for certain men to join classes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, derby is a physically tough, full contact sport that, in Kane's (1995, 194) terms, offers opportunities for women to 'experience their bodies as strong and powerful and free from male domination'. It is for these reasons that derby is often espoused as a 'feminist' sport (Finley 2010;Kearney 2011;Pavlidis and Connor 2016). Sailors (2013) affirms an emancipatory potential through a sweep of qualities characteristic of the sport and its subcultural scaffolding: (i) the sport's DIY character; (ii) a core aggression constitutive of the definition of masculinity and ideologically at odds with conventional femininity; (iii) simultaneous attachment to elements of conventional femininity such as the preceding revealing clothing; (iv) the extension of the said clothing to women of different body shapes and ages; (v) the parody of conventional femininity; (vi) inhospitality towards 'girl drama ' and (vii) the bonds between players.…”
Section: Roller Derbymentioning
confidence: 99%
“…Modern roller derby was conceived in 2001 as a women-only sport (Breeze, 2010; Sailors, 2013), and adherence to DIY and alternative ethics were an integral part of its development (Beaver, 2012; Pavlidis, 2012). Initially a space for women to have the freedom to be athletic and aggressive, whilst also part of a cooperative community, the sport of roller derby expanded to include men (Fletcher, 2014; Pavlidis and Connor, 2015). This involvement has not always been welcomed and men have frequently been reminded that they are a small minority within the sport; that roller derby is not ‘for’ them (D’Andrea, 2011; Proven, 2014).…”
Section: Social and Cultural Capital In Sportmentioning
confidence: 99%